Cytotoxic and anti-metastatic action mediates the anti-proliferative activity of Rhazya stricta Decne inducing apoptotic cell death in human cancer cells: Implication in chemopreventive mechanism - Ullah, Mohammad Fahad; M. Abuduhier, Faisel; H. Bhat, Showket; Ahmad, Aamir; Ajmal, Mohammad Rehan; Mustafa, Syed Khalid (Emirates Journal of Food and Agriculture, 2023)
Cancer is associated with a high rate of pre-mature mortality worldwide and serves as a significant impediment to extended life expectancy, leading to undesirable long-term effects on the quality of life of the patients. Bioactive chemical products derived from natural sources have an important place in the well-being of the human population since ancient times. Compounds derived from natural sources have dominated the drug discovery programs in the last five decades and comprise a substantial proportion of current-day pharmaceutical agents. Rhazya stricta, an evergreen shrub, it belongs to family Apocynaceae of order Gentianales, and the Rhazya stricta is known to have certain medicinal properties, as the Middle East and South Asian traditional medicine employed this plant as a cure for different diseases. Herein, the hydro-methanolic extract of Rhazya stricta Decne has been studied for its effect on spectrum of cancer cells, including LNCaP, C4-2B, PC-3 prostate cancer cells, MDA-MB-231, MCF-7, SKBR3 breast cancer cells, A-549 lung cancer cells and BxPC-3, MiaPaCa-2 pancreatic cancer. Hydro-methanolic extract of Rhazya stricta Decne in a dose-dependent manner, showed progressive inhibition of cell growth by induction of cell death in the treated human cancer cells. The IC value range for different breast cancer cell lines was 142-178 µg/ml; for prostate cancer cell lines, it was 90-148 µg/ml; for pancreatic cancer cell lines 116-166 µg/ml and for the lung cancer cells, it was reported to be 180 µg/ml. The anti-metastatic potential of extract was indicated by the notable reduction in invasiveness and cell migration. Moreover, the structurally diverse phytochemical rich extract, also downregulates the signaling of NF-kB and the NF-kB downstream target cytokine VEGF, providing an insight into the anticancer action mechanism. Keywords: Cell biology; Cancer chemoprevention; Anticancer drugs; Cell signaling; Natural compounds